﻿Profound purification of tellurium, zinc and cadmium for electronic applications - Vladimir N. Abryutin; Elena V. Davydova; Mikhail A. Egorov; Igor I. Maronchuk; Daria D. Sanikovich (Modern Electronic Materials, 2022)
A combined method of profound purification of Cd, Zn and Te developed by the Authors and allowing one to produce high-purity materials in a vertical reactor unit has been considered. The method includes the following processes: filtration refinement of metal alloy with the possibility of its vacuum degassing and additional purification through an oxide layer; first distillation with the possibility to use gettering additions in the melt and gettering filters; melt degassing with the removal of highly volatile impurities to the condenser in rough vacuum; second distillation and metal casting for weighed quantities. The Authors have developed and produced a test model of the unit for the experimental profound purification of metals using the method developed herein. Physical experiments have been conducted for obtaining 99,9999 wt.% purity Cd, Zn and Te for 30 residual impurities with a product yield of at least 55%.